Environmental experiences and positive environmental deviance towards environmental disclosure quality: a conceptual framework for internal corporate governance / Amar Hisham Jaaffar, Azlan Amran and Zeittey Karmilla Kaman - Jaaffar, Amar Hisham; Amran, Azlan; Kaman, Zeittey Karmilla
This paper presents a theoretical proposition based on an institutional theory for environmental disclosure quality. The argument is based on an internal behavioral governance mechanism, namely the cognitive influence of a board of directors’ and chief executive officer’s environmental experience on environmental disclosure quality using positive environmental deviance as the mediator. This paper contributes to the literature by providing a fundamental explanation of how organizations deviate positively from their peers who focus solely on external motivation for corporate environmental reporting practices, whereas the internal motivation, the cognitive influence of internal governance members, should be the focus for better environmental disclosure practices. The concept of positive environmental deviance is relatively new so it offers an interesting avenue for further research, especially in the context of developing countries. Overall, this paper sheds light on the internal behavioral governance mechanism and positive environmental deviance of environmental disclosure quality. This will hopefully attract researchers, practitioners and policy makers to view, more seriously, this area of concern.